PESANTREN SEBAGAI LEMBAGA PENDIDIKAN MULTIKULTURAL ISLAM-INDONESIA - Hamam Faizin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2013)
The emergence of the issue of terrorism in Indonesia uccusedly done by the Muslim students make many Muslim intellectuals interested to cunduct more studies. Because it is well known that the traditional boarding school is the oldest educational institution in Indonesia which is tolerant in differences and diversity. Based on the modern multicultural theory, this paper intends to prove the consistency of pesantren as an educational institution that teaches diversity which has always been the sound. Based on the descriptive analysis through literature study, it is found that as traditional educational institutions, pesantren teaches about the values ​​and traditions that reflect diversity. In addition, there are several elements emberio of tradition that encourages diversity, this is the mainstream schools, while the terrorist groups have nowhere to enter in.